USE OF BLENDED LEARNING TECHNOLOGIES IN TEACHING ENGINEERING MATERIALS SCIENCE DISCIPLINES - Нovorun , Tetiana; Belous , Olena; Berladir , Кhrystyna; Khaniukov , Kirill; Varakin , Vitaly (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The application of one of the popular forms of modern education for students of engineering specialties, «mixed learning», which combines distance learning in today's conditions and traditional classroom learning, is considered. The implementation of mixed learning technology is considered in the example of a course for materials science students at Sumy State University through an environment with the use of computer technologies of the MIX, which unites all educational resources of the university.